CTA's Annual Report highlights poverty reduction - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'Whilst economic growth per se is a necessary requirement for tackling rural poverty, it is insufficient' writes Director Dr R D Cooke in his introduction to the 1998 CTA Annual Report. Two other essential components of a poverty focus are, he...